Research progress of fire blight in fruit trees - FANG Xi; XU Youping; CAI Xinzhong (浙江大学学报. 农业与生命科学版)
Fire blight is an important disease caused by Gram-negative bacterium Erwinia amylovora that severely harms Rosaceae plants, and it is an important factor to restrict the development of pear and apple industries in China. Erwinia amylovora is highly virulent with a wide host range, and thus it is difficult to find a unified target for its eradication. With the emergence of drug-resistant strains, control of the disease becomes more difficult. In this paper, the disease characteristics, epidemiology, management methods and the mechanisms underlying E. amylovora pathogenicity and plant resistance were reviewed, which could provide references to further research and efficient control of fire blight.